PENERAPAN GAME-BASED LEARNING DALAM MENINGKATKAN MOTORIK HALUS ANAK ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) - Firdatun Fauziah; Miftahul Aula Sa’adah; Mulyani Mulyani (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Children with Attention Deficit Hyperactivity Disorder (ADHD) generally experience difficulties in fine motor skills, which affect their learning activities and daily independence. This study aims to apply a Game-Based Learning (GBL) approach using playdough as a learning strategy to improve the fine motor skills of children with ADHD at the Teratai Putih Integrated Inclusive Early Childhood Education Centre in Banjarbaru City. The research method used was the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, but this study was only conducted up to the implementation stage. The research subjects consisted of three children with ADHD aged 4–6 years. Data were collected through observation, interviews, and documentation, then analysed descriptively and qualitatively. The results of the study indicate that the implementation of playdough-based Game-Based Learning can improve hand coordination, finger flexibility, and the precision of movements in children with ADHD. Activities such as rolling, shaping, cutting, and arranging playdough help hone pre-writing skills and improve children's focus in completing tasks. Each child shows different progress according to their individual characteristics and attention levels. A conducive learning environment, individual guidance, and clear and repeated instructions have been proven to increase children's engagement and motivation in the learning process. Thus, Game-Based Learning can be an effective alternative approach to improve the fine motor skills of children with ADHD while fostering learning motivation and focus. This method also supports the principle of inclusive education by providing a learning experience that is enjoyable, interactive, and adaptive to the specific needs of children. This study recommends the use of sensorimotor games such as playdough in learning activities in inclusive schools, as well as further research with a larger number of subjects to measure the long-term effectiveness of this method.